2008
DOI: 10.1128/aac.01122-07
|View full text |Cite
|
Sign up to set email alerts
|

Entecavir for Treatment of Hepatitis B Virus Displays No In Vitro Mitochondrial Toxicity or DNA Polymerase Gamma Inhibition

Abstract: Therapy with nucleoside reverse transcriptase inhibitors (NRTIs) can be associated with mitochondrial toxicity. In vitro studies have been used to predict the predisposition for and characterize the mechanisms causing mitochondrial toxicity. Entecavir (ETV) is an approved deoxyguanosine nucleoside for the treatment of chronic hepatitis B virus (HBV) infection that exhibits potent activity against viral reverse transcriptase. We assessed the potential for mitochondrial toxicity of ETV in long-term cultures of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 36 publications
4
42
0
Order By: Relevance
“…4). Consistent with previous reports (21,24), exposure of cells to ddC at 10 M resulted in significant increases in extracellular lactate levels (P Ͻ 0.001), indicating impaired mitochondrial function.…”
Section: Cytotoxicity and Evaluation By Electron Microscopy Of Mitochsupporting
confidence: 80%
See 2 more Smart Citations
“…4). Consistent with previous reports (21,24), exposure of cells to ddC at 10 M resulted in significant increases in extracellular lactate levels (P Ͻ 0.001), indicating impaired mitochondrial function.…”
Section: Cytotoxicity and Evaluation By Electron Microscopy Of Mitochsupporting
confidence: 80%
“…The effects of PNA and other nucleoside analogs were assessed in HepG2 cell cultures essentially as described previously (21,28). The compounds or dimethyl sulfoxide (DMSO) vehicle control was added from DMSO stocks at 1,000 times the final exposure concentration.…”
Section: Test Compound Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, woodchucks can carry plague and therefore are difficult to be imported into China. As a result, our study used rhesus monkeys as the sensitive animals, with an attempt to establish rhesus monkey model for mitochondrial toxicity evaluation [21][22][23][24][25] . Mitochondrial toxicities are relatively tissue-specific and drug-specific.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, entecavir may also develop another form of myopathy. Yuan et al 13 reported a patient with entecavir-associated myopathy, in whom the muscle histopathology showed an inflammatory change, but not mitochondrial toxicity.…”
mentioning
confidence: 99%